Diatom distribution and long-term survival in a heavily polluted sediment core from the Bay of Bagnoli (Tyrrhenian Sea, Italy) - PELUSI, ANGELA; ROMERO MARTÍNEZ, MARÍA LORENA; MULE, APURVA; SCALCO, ELEONORA; BARRENECHEA ANGELES, INES; PIREDDA, ROBERTA; KOOISTRA H.C.F. , WIEBE; MONTRESOR, MARINA; SARNO, DIANA (Mediterranean Marine Science, 2025)
Diatom resting stages can remain viable in sediments for decades and germinate when exposed to suitable environmental conditions, inoculating the water column and the surface sediments with new populations of cells. Classical methods, based on acid-cleaning of diatom frustules in sediment samples, do not discriminate between living and dead cells and may destroy the more fragile taxa. We used a metabarcoding dataset based on the V9 region of the 18S rRNA (20,602 reads, 102 diatom Amplicon Sequence Variants (ASV)) coupled with the Serial Dilution Culture method to assess diversity and viability of resting stages in a heavily polluted sediment core from the Bay of Bagnoli (Tyrrhenian Sea) spanning approximately two centuries. Our results indicate that planktonic centric diatoms dominated the sediment layers, but ASVs of benthic pennates were also present, especially in older layers. High densities (up to ~2·106 cells g-1 wet sediment) of viable cells were recorded in the surface layer (dated to 2013) for Nanofrustulum shiloi and for a small unidentified pennate diatom. Concentrations of living cells decreased towards older layers, but cultures of Chaetoceros curvisetus were still generated from a layer dated to 1954. Selected strains were characterized morphologically, in light and electron microscopy, and molecularly, confirming the records of N. shiloi, Psammogramma sp. and Plagiogramma sp. The results of our study highlight the capability of several centric and pennate diatom species to ‘rest’ alive in severely polluted sediments for decades. This calls for future studies aimed at understanding the mechanisms that regulate dormancy and the adaptation to harsh environmental conditions, which have potential biotechnological applications.